Determining the tempo of exhumation in the eastern Himalaya: Part 2. Integrating bedrock and detrital cooling ages through thermokinematic modelling. (20th September 2021) - Braza, Mary; McQuarrie, Nadine
Abstract: The exhumation record of a fold‐thrust belt is preserved by thermochronologic minerals, such as zircon and apatite, both in exposed bedrock and in synorogenic sedimentary rocks in the foreland basin. Treating these as separate records can lead to potentially contrasting interpretations of a single exhumation history. Integrating the bedrock and detrital records with thermokinematic models of sequential deformation of a fold‐thrust belt can identify viable exhumation pathways of the bedrock and elucidate both how bedrock exhumation varies in space and time and how accurately the basin records exhumation changes in the source region. Predicted bedrock cooling ages and modelled basin thickness are used to estimate the amount and source of sediments supplied to the foreland basin during each increment of deformation to predict the detrital cooling signal over time. Applying this integrated bedrock‐detrital model to a cross‐section in Arunachal Pradesh, NE India demonstrates spatial and temporal variability in exhumation, with a background exhumation rate of <2 mm/yr, periods of rapid exhumation at rates of 3–7 mm/yr, and short pulses of 10–12 mm/yr rates during out‐of‐sequence thrusting. Our results predict that the detrital apatite fission track (DAFT) system records a constant lag time of 0.5–1 Myr. Although the response of the detrital zircon fission track (DZFT) system is more complex, the system records changes in lag time (1–5 Myr) as a function of the kinematics, deformation rates and thermal profile of the crust in the hinterland. However, the DZFT cooling signal is delayed by 1–2 Myr relative to the age of marked shifts in location, magnitude and rate of exhumation in the source region. Our models also highlight the importance of recycled foreland deposits in matching the ca. 20 Ma static peak in the DZFT record and ca. 14 Ma static peak in the DAFT record. Abstract : Integrating bedrock and detrital cooling ages with thermokinematic models of sequential deformation of a balanced cross‐section reveals spatial and temporal variations in exhumation rates in Arunachal Pradesh, NE India. Predicted detrital apatite fission track ages record a constant lag time, while predicted detrital zircon fission track ages record changes in lag time as a function of the kinematics, deformation rates, and thermal profile of the crust in the source region.